2018
DOI: 10.1021/jacs.8b07560
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Dichotomy of Mixed Halide CH3NH3Pb(Br1–xClx)3 Single Crystals: Surface versus Bulk Photoluminescence

Abstract: In this work, the spatially dependent recombination kinetics of mixed-halide hybrid perovskite CHNHPb(BrCl ) (0 ≤ x ≤ 0.19) single crystals are investigated using time-resolved photoluminescence spectroscopy with one- and two-photon femtosecond laser excitation. The introduction of chloride by substituting a fraction of the bromide leads to a decreased lattice constant compared to pure bromide perovskite ( x = 0) and a higher concentration of surface defects. The measured kinetics under one-photon excitation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 62 publications
4
23
0
Order By: Relevance
“…Such dichotomy between extrinsic (surface) and intrinsic (bulk) effects of halide substitution in lead bromide perovskites was also reported in another kind of mixed halide single crystal (MAPb(Br x Cl 1−x ) 3 ) observed by the contrast between one-and two-photon excitation. [129] More recently, Wang and coworkers showed that photo-induced phase segregation in CsPb(Br x I 1−x ) 3 microplatelets can be significantly mitigated by simple surface passivation of covering a thin layer of PMMA, as shown in Figure 9D. [9] Lai et al studied anion interdiffusion in CsPbCl 3 -CsPbBr 3 single-crystalline perovskite nanowire heterojunctions fabricated via anion exchange chemistry, [130] as shown in Figure 9E, which directly visualize the intrinsic anionic inter-diffusion between Cl/Br rich ends of nanowire at elevated temperature, and reveal a mechanism of halide vacancies assisted ion migration via PL lifetime mapping and molecular simulation.…”
Section: Phase Segregation and Interdiffusion Of Mobile Ions In Mixedmentioning
confidence: 99%
See 1 more Smart Citation
“…Such dichotomy between extrinsic (surface) and intrinsic (bulk) effects of halide substitution in lead bromide perovskites was also reported in another kind of mixed halide single crystal (MAPb(Br x Cl 1−x ) 3 ) observed by the contrast between one-and two-photon excitation. [129] More recently, Wang and coworkers showed that photo-induced phase segregation in CsPb(Br x I 1−x ) 3 microplatelets can be significantly mitigated by simple surface passivation of covering a thin layer of PMMA, as shown in Figure 9D. [9] Lai et al studied anion interdiffusion in CsPbCl 3 -CsPbBr 3 single-crystalline perovskite nanowire heterojunctions fabricated via anion exchange chemistry, [130] as shown in Figure 9E, which directly visualize the intrinsic anionic inter-diffusion between Cl/Br rich ends of nanowire at elevated temperature, and reveal a mechanism of halide vacancies assisted ion migration via PL lifetime mapping and molecular simulation.…”
Section: Phase Segregation and Interdiffusion Of Mobile Ions In Mixedmentioning
confidence: 99%
“…Such dichotomy between extrinsic (surface) and intrinsic (bulk) effects of halide substitution in lead bromide perovskites was also reported in another kind of mixed halide single crystal (MAPb(Br x Cl 1− x ) 3 ) observed by the contrast between one‐ and two‐photon excitation. [ 129 ] More recently, Wang and coworkers showed that photo‐induced phase segregation in CsPb(Br x I 1− x ) 3 microplatelets can be significantly mitigated by simple surface passivation of covering a thin layer of PMMA, as shown in Figure 9D. [ 9 ] Lai et al.…”
Section: Mobile Ion Transport and Phase Segregationmentioning
confidence: 99%
“…In our experiments, the probe wavelength was set to 745 nm, which is within the strong transient gain peak near the band edge as determined by previous fs-TA spectroscopy [35] . For this probe wavelength, our experimental setup restricted the pump to a longer wavelength, here 817 nm, which is below the band gap of these perovskite samples (see Figure S2 for representative linear absorption and emission spectra), but excitation of photo-generated carriers is still possible via multi-photon absorption processes [36][37][38][39] (see the supplementary information for details of the excitation conditions). Previous results demonstrate that the resulting TA spectra under two-photon excitation are similar to those under single-photon excitation [40] .…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, introducing new concepts might be necessary to overcome the unique research challenges encountered in the study of the HaP materials. As suggested by Zhu et al.,, HaPs could be treated as “crystalline liquid” as they belong to the phonon glass electron crystals family due to their binary structure formed by a PbX 3 ‐sublattice (which forms a cage) and a weakly bound A + cation sublattice. The particular nature of these materials leads to the stark contrast in the charge carrier and phonon transport properties.…”
Section: Conclusion and Perspectivementioning
confidence: 99%